1998
DOI: 10.1007/s004010050930
|View full text |Cite
|
Sign up to set email alerts
|

Upper motor neuron predominant degeneration with frontal and temporal lobe atrophy

Abstract: The autopsy findings of a 78-year-old man mimicking primary lateral sclerosis (PLS) are reported. He showed slowly progressive spasticity, pseudobulbar palsy and character change, and died 32 months after the onset of symptoms. Autopsy revealed severe atrophy of the frontal and temporal lobes, remarkable neuronal loss and gliosis in the precentral gyrus, left temporal lobe pole and amygdala, mild degeneration of the Ammon's horn, degeneration of the corticospinal tract, and very mild involvement of the lower m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 16 publications
4
27
0
Order By: Relevance
“…They also show that unlike neurons the quantitative assessment of these inclusions may be a neuropathological marker of disease duration. The presence of ubiquitin-positive tau-negative intraneuronal inclusions within the cerebral cortex and subcortical structures has been long considered as a key neuropathological feature of MND with dementia [16,45] or FTD with MND [3,5,7,9,11,17,23,27,31,39,42,46]. Despite several contributions based on small series, the presence of ubiquitin-related pathology within the cerebral cortex is still considered a rare phenomenon in typical FTD cases [2,6,15,18,21,22,24,34,35,40,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…They also show that unlike neurons the quantitative assessment of these inclusions may be a neuropathological marker of disease duration. The presence of ubiquitin-positive tau-negative intraneuronal inclusions within the cerebral cortex and subcortical structures has been long considered as a key neuropathological feature of MND with dementia [16,45] or FTD with MND [3,5,7,9,11,17,23,27,31,39,42,46]. Despite several contributions based on small series, the presence of ubiquitin-related pathology within the cerebral cortex is still considered a rare phenomenon in typical FTD cases [2,6,15,18,21,22,24,34,35,40,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural changes with bilateral atrophy of the frontal and temporal lobes have been reported in association with PLS in one patient (16). Frontal lobe dysfunction has been evidenced in PLS by magnetic resonance imaging (MRI) studies (17,18), and positron emission tomography (PET) and single photon emission computed tomography (SPECT) studies (4,12,19).…”
Section: Introductionmentioning
confidence: 96%
“…The relationship between PLS and other neurodegenerative diseases has been a subject of debate ever since the description in PLS of neuropsychological impairment (10,13), ocular movement abnormalities (14,15), cortical atrophy (9,10,16) and intellectual impairment (10). Behavioural changes with bilateral atrophy of the frontal and temporal lobes have been reported in association with PLS in one patient (16).…”
Section: Introductionmentioning
confidence: 99%
“…Pathological features of PLS are neuronal loss in the precentral gyrus with corticospinal tract degeneration and preservation of the lower motor neurons. On the other hand, it was also reported that ubiquitin-positive neuronal cytoplasmic inclusions [13,14], TAR DNA-binding protein of 43 kDa (TDP-43)-positive inclusions [15], and Bunina bodies can be also found in the lower motor neurons as well as in the precentral gyrus in some clinically PLS cases [16][17][18][19]. Based on these findings, it is considered that at least some of the PLS cases may be a clinicopathological subtype of amyotrophic lateral sclerosis.…”
Section: Introductionmentioning
confidence: 98%